Automatic Transfer Switch (ATS) for Solar Powered Street Lighting (PJU) (Case Study: Aminggaru Ilaga Airport, Central Papua) - Ramadhani Ernanda Daulay; Ahmad Dhani; Beni Satria (INFOKUM, 2026)
Solar-powered Public Street Lighting (PSL) is an environmentally friendly lighting solution that is widely implemented in remote areas as well as strategic locations. However, the reliability of solar-powered street lighting systems often faces challenges due to dependency on weather conditions and limited battery capacity, which can cause the lights to turn off before the end of the operational period. This study aims to design and evaluate an Automatic Transfer Switch (ATS) system as an automatic power source switching mechanism to improve the reliability of solar-powered street lighting. The proposed system utilizes a Solar Power Generation System (SPGS) as the primary power source and the utility grid (PLN) as a backup source. Testing was conducted using street lighting loads of 10 Watt and 20 Watt lamps, with observed parameters including battery voltage, charging current, load voltage and current, and ATS switching time. The test results show that the solar power system is capable of supplying street lighting for an average duration of approximately ±10 hours and 50 minutes per night. The ATS switches to the utility grid when the battery voltage drops to 11.6 VDC and switches back to the solar power system once the primary source becomes stable again. The switching process is characterized by a brief voltage drop, which is a normal characteristic of ATS operation designed to ensure system safety and prevent electrical disturbances. Based on the experimental results, it can be concluded that the implementation of an Automatic Transfer Switch (ATS) in solar-powered street lighting systems effectively enhances lighting continuity, system reliability, and component protection, making it suitable for application in airport environments and other areas requiring high lighting reliability.